PERAN BUDAYA ORGANISASI DALAM MENINGKATKAN PELAYANAN PUBLIK DI ERA DIGITAL - Sri Najwa Kusuma; Abdurohim (PT. Hasba Edukasi Mandiri, 2025)
The digital era has brought significant changes to public service delivery, requiring government organizations to be more responsive, transparent, and efficient. This study explores the role of organizational culture in improving the quality of public services amidst digital transformation. A strong organizational culture—built on values such as commitment, innovation, and collaboration—has proven effective in enhancing employee performance and fostering a work environment that supports optimal service delivery. The study also identifies several challenges in developing an adaptive organizational culture, including resistance to change and inadequate training. Using a descriptive approach and literature review, this study concludes that the success of public services in the digital era is heavily influenced by how well organizational culture can adapt to the dynamics of the time. Therefore, strengthening organizational culture in alignment with digital transformation is essential for effective and sustainable public service delivery.